An Investigation Metaphor and Simile used in the Series of Harry Potter by Joanne Kathleen Rowling - Nguyễn Thị Diệu Linh (2012)
This study investigated into the syntactic, semantic and pragmatic features of metonymic expressions in English and Vietnamese short stories. This is a descriptive study executed in a contrastive analysis with …